2022
DOI: 10.3389/fmed.2022.922431
|View full text |Cite
|
Sign up to set email alerts
|

Daily, self-test rapid antigen test to assess SARS-CoV-2 viability in de-isolation of patients with COVID-19

Abstract: BackgroundIsolation of COVID-19 patients is a crucial infection control measure to prevent further SARS-CoV-2 transmission, but determining an appropriate timing to end the COVID-19 isolation is a challenging. We evaluated the performance of the self-test rapid antigen test (RAT) as a potential proxy to terminate the isolation of COVID-19 patients.Materials and methodsSymptomatic COVID-19 patients were enrolled who were admitted to a regional community treatment center (CTC) in Seoul (South Korea). Self-test R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Test positivity (new infections detected). Across twenty studies, new infections detected by COVIDST varied from 0.02% to 27% [22,25,27,28,31,[36][37][38][39][40][41][42][43][44][45][46][47][48]. In two other studies, test positivity varied from 12% to 83.3% during the delta wave and 41.7% to 87.2% during the omicron wave [29,49].…”
Section: Synthesized Results For Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Test positivity (new infections detected). Across twenty studies, new infections detected by COVIDST varied from 0.02% to 27% [22,25,27,28,31,[36][37][38][39][40][41][42][43][44][45][46][47][48]. In two other studies, test positivity varied from 12% to 83.3% during the delta wave and 41.7% to 87.2% during the omicron wave [29,49].…”
Section: Synthesized Results For Secondary Outcomesmentioning
confidence: 99%
“…Conversely, a community-based study reported sensitivity of 23% within 0–1 days and 66.67% within 2–4 days of symptom onset [ 23 ]. Finally, another study reported a sensitivity of 73% when self-test was conducted within 0–5 days of symptom onset as compared to 22% when conducted after 5 days [ 27 ].…”
Section: Resultsmentioning
confidence: 99%